ANALISIS SMART MANUFACTURING DALAM PERANCANGAN NANOKOMPOSIT POLIMER BERBASIS DATA: BLIBIOMETRIC ANALYSIS - Erza Arkan Zharif; Bani Septiawan; Akbar Abdillah (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
This study aims to analyze research trends and directions in smart manufacturing for data-driven polymer nanocomposite design using a bibliometric approach. Data were obtained from the Scopus database, comprising a total of 3,933 documents published between 2022 and 2026, limited to the Engineering subject area, article document type, and English language. The analysis was conducted using VOSviewer software to map collaboration networks, keyword co-occurrences, and thematic evolution. The results indicate a stable publication trend from 2022 to 2024, followed by a decline in 2025–2026, suggesting an early maturity phase and a shift toward the integration of artificial intelligence and data analytics. Dominant keywords such as nanocomposites, polymer matrix composites, and graphene highlight research focus on smart material innovation. This study provides a comprehensive overview of scientific developments and serves as a foundation for defining future research directions in sustainable digital manufacturing.